بەها ئاینییەکان و تایبەتمەندی سیماکانی کەسێتی کۆمەڵگەی کوردی توێژینەوەیەکی تیۆری شیکارییە توێژینەوەی هەڵێنجراوی ماستەر - عبداللە, ئاسۆ ئیبراهیم; محمد, شفیع صابر (Sulaimani Journal for Humanities, 2022)
This study discusses the role of the values of Islam in the structure of the personality of the individual in Kurdish society, as religion has its own special significance in all sphere of human life, whether as indivduals or as asociety. It discusses the values, that are common in Kurdish society to this day, although discusses the impact of each of these values on the personal identities of Kurdish society, and then discusses the testimony and testimony of Orientalists, psychologists, and sociologists in Kurdish personalities in the the past and present. The most important results of this study have been obtained, including: 1- Despite rapid changes in technology and materials, the spiritual and meaningful aspects of Kurdish society still remain valuable. 2- I ndividuals in Kurdish society have a significant commitment to religious values, wich are still a major factor in the well-being and happiness of individuals in Kurdish society. The key words in this study are: (value, religion, personality,trait, Kurd).